2020
DOI: 10.2147/oarrr.s231667
|View full text |Cite
|
Sign up to set email alerts
|

<p>Treatment with Repository Corticotropin Injection in Patients with Rheumatoid Arthritis, Systemic Lupus Erythematosus, and Dermatomyositis/Polymyositis</p>

Abstract: Purpose: Repository corticotropin injection (RCI) is indicated for a number of autoimmunemediated diseases including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and dermatomyositis (DM)/polymyositis (PM). To better understand the practice patterns and outcomes of RCI in patients with RA, SLE, or DM/PM, we conducted a retrospective medical record analysis. Patients and Methods: Participating providers selected deidentified medical records of patients meeting the inclusion criteria (age ≥18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…28 Additional real-world outcome studies show that osteoarthritis is a prevalent comorbidity in patients with RA treated with RCI. 15,29,30 In addition, the presence of more tender than swollen joints may reflect the coexistence of osteoarthritis in this patient population. 31 Clinical measures of disease severity, including CDAI and number of tender or swollen joints, indicated that patients had high RA activity prior to starting RCI therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Additional real-world outcome studies show that osteoarthritis is a prevalent comorbidity in patients with RA treated with RCI. 15,29,30 In addition, the presence of more tender than swollen joints may reflect the coexistence of osteoarthritis in this patient population. 31 Clinical measures of disease severity, including CDAI and number of tender or swollen joints, indicated that patients had high RA activity prior to starting RCI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The RCI duration estimate (152±117 days) likely underestimates the total duration, as the time under treatment for the last prescription cannot be determined; however, our findings are consistent with other published reports characterizing the duration of RCI treatment in clinical practice in which the mean duration of treatment was 4.8 months. 29 Several recent publications support the use of RCI in patients for whom ACR-recommended RA therapies (glucocorticoids, csDMARDs, tsDMARDs, and bDMARDs) lack efficacy, for acute exacerbation of disease, or for use as an add-on therapy. 17,29,30,33 Retrospective analysis of patients with refractory RA demonstrated a significant improvement in physician impression of change after short-term RCI therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Repository corticotropin injection (RCI; Acthar ® Gel, Mallinckrodt ARD LLC, Bedminster, NJ, USA)—a naturally sourced complex mixture of adrenocorticotropic hormone analogs and other pituitary peptides—is indicated for short-term administration in patients experiencing acute episodes or exacerbations of RA [ 15 ]. Evidence from previous studies suggests that in clinical practice, RCI is used primarily as late-line therapy to treat flares, as a bridge to new therapy, or as an add-on to prior therapy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 18 A retrospective chart review study reported that 78% of RA patients treated with RCI had an improvement based on physician assessment. 19 An observational administrative claims-based analysis of treatment patterns, healthcare utilization, and cost of RCI in patients with RA suggests a potential for a reduction in medical service use and associated costs with RCI by approximately 33%. 20 Together these data suggest a potential for improvement in patient’s health outcomes and an overall reduction in cost for disease management.…”
Section: Introductionmentioning
confidence: 99%